Kontrak No.: KKR/IKR/IP/UB/22/99 : Pembinaan Jambatan Batang Rajang, Sibu, Sarawak, PROGRESS REPORT NO. 17 - Universiti Malaysia Sarawak, Research & Innovation Management Centre (RIMC) (Jabatan Kerja Raya Sarawak, 2000)
This monthly report has been prepared with the objective of outlining the progress of works for the Proposed Jambatan Batang Rajang Project Contract for the period from 1st August 2000 to 31st August 2000.